Household Use of Tanana Valley Forest Resources: An Economic and Geographical Approach (Based on Data from the Tanana Valley Forest Use Survey) - Бояр, Андрій Олексійович; Boiar, Andrii O. (My University, 2004)
Tanana Valley Forest Use Survey was the first attempt to gather information about the forest resources use by households in Alaska. The original study was designed to analyze and interpret the data provided by the Survey. The paper discusses the environmental and socio-economic factors determining the forest resources use in the Tanana Valley by the residents of the region. The minimum replacement values for the various categories of forest resources harvested in the region during the period from September 2002 to August 2003 are calculated and discussed. A series of stationary maps representing the allocation of the harvested forest resources were drawn. To reveal the relationship between the households’ harvesting effort (amount harvested) and certain socio-economic household characteristics the cluster analysis and linear regression techniques were employed. No linear relationship between the two groups of the variables was determined in any resource category. However, cluster analysis shows certain non-linear relationships between the variables of income, time of Alaska residence, number of household members, education and the value of harvested by the households forest resources.
This is a manuscript of my Master Thesis defended at the University of Alaska at Fairbanks in 2004
Keywords: Tanana Valley; Alaska; forest use; survey; households; forest resources